2021
DOI: 10.1021/acs.jafc.1c01091
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Roles of Mesoporous Silica in Safe Pesticide Application by Nanotechnology: A Review

Abstract: Pollution related to pesticides has become a global problem due to their low utilization and non-targeting application, and nanotechnology has shown great potential in promoting sustainable agriculture. Nowadays, mesoporous silica-based nanomaterials have garnered immense attention for improving the efficacy and safety of pesticides due to their distinctive advantages of low toxicity, high thermal and chemical stability, and particularly size tunability and versatile functionality. Based on the introduction of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(42 citation statements)
references
References 235 publications
0
42
0
Order By: Relevance
“…All of these formulations have a high loading capacity and sustainable release behavior, but none of them allow the pesticide applicator to regulate when and where the pesticide is released. On the other hand, there are many new controlled release formulations (CRFs) that focus on the on-demand pesticide release with specific release triggers such as pH, , light, redox potential, and enzymes as a cargo release liberator.…”
Section: Introductionmentioning
confidence: 99%
“…All of these formulations have a high loading capacity and sustainable release behavior, but none of them allow the pesticide applicator to regulate when and where the pesticide is released. On the other hand, there are many new controlled release formulations (CRFs) that focus on the on-demand pesticide release with specific release triggers such as pH, , light, redox potential, and enzymes as a cargo release liberator.…”
Section: Introductionmentioning
confidence: 99%
“…The durability of the pesticide formulation, a measure of the length of time that a pesticide–carrier complex maintains its integrity after application, is considered a key parameter for environmental risk assessment of pesticide formulations. ,, The value of durability determines whether further decisions regarding both exposure risks and hazard evaluation of pesticide residues are necessary to be made. Different from the common knowledge that the sustained/controlled-release carrier may restrict the dissipation of pesticide, the relatively short durability of SCM in SCCS is obtained in our work.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Environmental behaviors of pesticide residues associated with their adsorption and degradation in a soil system are important factors that affect the fate of pesticides. 4,28 Thompson et al observed that the dissipation of spinosad residues in exposed sandy loam soils in central Ontario of Canada followed hyperbolic or exponential decline models. 29 Sharma et al 30 and Adak et al 31 also found that the dissipation of spinosad from soil under subtropical conditions obeyed the first-order kinetics.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, improving the utilization of pesticides has been a crucial issue over the past decade. Recently, with the rapid development and application of nanotechnology in the agricultural field, a series of environmental-stimulus-responsive pesticide nanosystems [ 5 , 6 , 7 ], such as pH [ 8 , 9 , 10 ], temperature [ 11 , 12 , 13 , 14 ], enzyme [ 15 , 16 , 17 ], redox [ 18 , 19 , 20 ], and light-responsive materials [ 21 , 22 , 23 ], were developed to improve the utilization rate of pesticides and reduce environmental risk. However, to the best of our knowledge, few reports on dual-responsive pesticide delivery nanosystems exist.…”
Section: Introductionmentioning
confidence: 99%